INTERCONNECTIVITY OF EPILEPSY AND DEPRESSIVE DISORDERS AND THEIR CORRECTION (Conferencea, 2022)
Anxiety-depressive syndrome is a common comorbidity in epilepsy. The presence of depression in a patient leads to a worsening of the course of epilepsy, the development of repeated and frequent seizures, which leads to an increase in the number of lethality in this pathology.